Visibility challenges for Asian scientists - Hanasoge, Shravan; Horiuchi, Noriaki; Huang, Congcong; Jia, Hepeng; Kim, Na Young; Murao, Mio; Seo, Minah; Tan, Rebecca; Wilkinson, Jens (SPRINGERNATURE, 2020)
Nine researchers, editors and science communicators share their views about the barriers that Asian scientists encounter in publishing their work and becoming more visible on the international level. The contributorsShravan Hanasoge has been a faculty member in the Department of Astronomy and Astrophysics at the Tata Institute of Fundamental Research, Mumbai, since 2013. He received his Ph.D. at Stanford University and then pursued a postdoctoral fellowship at the Max Planck Institute for Solar System Research and the Department of Geosciences, Princeton University.Noriaki Horiuchi is a senior editor at Nature Photonics, based in the Springer Nature Tokyo office. He obtained a Ph.D. from Universite Joseph Fourier, Grenoble, and then pursued postdoctoral research at Toyota Technological Institute and RIKEN. He joined Nature Photonics in 2009.Congcong Huang is a team manager and senior editor at Nature Communications, based in the Springer Nature Shanghai office. She obtained a Ph.D. from the University of Cambridge, UK, then pursued postdoctoral research at Stanford University and SLAC National Accelerator Laboratory in the USA. She joined Nature Communications in 2012.Hepeng Jia is a science communication researcher at the School of Communication, Soochow University in China and a science journalist, writing for the Nature journals and Chemical & Engineering News. He has a Ph.D. in science communication from Cornell University.Na Young Kim is an associate professor at the Institute for Quantum Computing, University of Waterloo, Canada, leading her Quantum Innovation laboratory. She has a Ph.D. from Stanford University and has also worked in industry for Apple Inc.Mio Murao is a professor at the Department of Physics, School of Science, The University of Tokyo, Japan. She has a Ph.D. from Ochanomizu University in Japan, then pursued postdoctoral research at Harvard University, Imperial College London and RIKEN before joining the University of Tokyo as a faculty member.Minah Seo is principal research scientist at the Sensor System Research Center, Korea Institute of Science and Technology, South Korea. She has a Ph.D. from Seoul National University, then pursued postdoctoral research at Los Alamos National Laboratory, USA.Rebecca Tan is the Editor in Chief of Asian Scientist Magazine, a science and technology magazine that highlights research and development news stories from Asia to a global audience. She has a Ph.D. from the National University of Singapore.Jens Wilkinson is communications officer at the International Affairs Division in RIKEN, Japan. He has been working in Japan for over 15 years.
Keywords: SOCIAL MEDIA